2013
DOI: 10.1109/tbme.2013.2250286
|View full text |Cite
|
Sign up to set email alerts
|

Markerless Motion Capture and Measurement of Hand Kinematics: Validation and Application to Home-Based Upper Limb Rehabilitation

Abstract: Dynamic movements of the hand, fingers, and thumb are difficult to measure due to the versatility and complexity of movement inherent in function. An innovative approach to measuring hand kinematics is proposed and validated. The proposed system utilizes the Microsoft Kinect and goes beyond gesture recognition to develop a validated measurement technique of finger kinematics. The proposed system adopted landmark definition (validated through ground truth estimation against assessors) and grip classification al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(60 citation statements)
references
References 30 publications
1
49
0
Order By: Relevance
“…The Kinect is also being used for the assess ment of postural control [30], gait [31], balance [3], static foot posture [32], body sway [33], and common motor movements [34], all with promising comparisons to three-dimensional gold standard systems. The use of the Kinect as a rehabilitation tool outside of the clinic and in the home [35][36][37] suggests the sensor's portability and supports the recommendation of previous research to incorporate assessment throughout the continuum of care [38].…”
Section: Microsoft Kinectsupporting
confidence: 59%
“…The Kinect is also being used for the assess ment of postural control [30], gait [31], balance [3], static foot posture [32], body sway [33], and common motor movements [34], all with promising comparisons to three-dimensional gold standard systems. The use of the Kinect as a rehabilitation tool outside of the clinic and in the home [35][36][37] suggests the sensor's portability and supports the recommendation of previous research to incorporate assessment throughout the continuum of care [38].…”
Section: Microsoft Kinectsupporting
confidence: 59%
“…The system developed by Metcalf, et al [17] is used to capture and measure hand kinematics, and can be employed for home-based upper limb rehabilitation. Besides, Kitsunezaki, et al [18] reported four types of Kinect-based physical applications to measure useful parameters such as walking time or joint angle ranges, to determining training effectiveness.…”
Section: Research Jiann-der Leementioning
confidence: 99%
“…The rehabilitation exercises are commonly performed in a rehabilitation center, and the physiotherapist identifies and evaluates the movements and motor functions that are being affected. In order to achieve kinetic gains as quickly as possible, patients are encouraged to perform the same exercise movements several times [26]. Patients' learning by movement repetition is crucial for their successful therapy.…”
Section: Rehabilitation Exercisesmentioning
confidence: 99%